Pro and anti-inflammatory cytokine levels (TNF-α, IL-1β, IL-6 and IL-10) in rat model of neuroma. Issue 3 (September 2017) - Khan, Junad; Noboru, Noma; Young, Andrew; Thomas, Davis
Abstract: Traumatic neuroma is neuronal tissue proliferation developed in a nerve injury site, often associated with increased sensitivity and spontaneous or evoked neuropathic pain. The mechanisms leading to the disorganized nerve proliferation are not completely understood, though inflammation in the injured nerve vicinity most likely has a role in the process. Inflammatory cytokines are also known to be involved in the maintenance and development of post-traumatic and neuropathic pain. The goal of this study was to quantify and compare pro and anti-inflammatory cytokines (TNF-α, IL-1β, IL-6 and IL-10) levels in nerves that formed neuromas and nerves that did not, following sciatic nerve transection. A total of 30 rats were used in this study. Twenty rats underwent sciatic nerve transection and 10 underwent sham surgery. Six weeks post-surgery nerve sections were collected and histologically evaluated for neuroma formation. The samples were then classified as neuroma, non-neuroma and sham groups. TNF-α, IL-1β, IL-6 and IL-10 levels were measured in the nerves employing ELISA. TNF-α levels were significantly higher in both neuroma and non-neuroma-forming injured nerves compared to the sham group. IL-1β and IL-6 levels were significantly higher in the neuroma-forming nerves compared to the sham group. IL-10 levels were significantly higher in the non-neuroma group compared to the sham group. In conclusion IL-6, and IL-1 β may have a role in the formation of traumatic neuroma while IL-10 may inhibit neuroma formation.